Cooperation between Branches of Power of the Russian Federation and the Republic Of Armenia as the Basis of Implementation of Foreign Policy Courses on Military Security - Ekaterina Sergeevna Andreeva (Управленческое консультирование)
The article investigates the interaction of various authorities of the Russian Federation and the Republic of Armenia in the sphere of military security. The systematic character of the actions taken by the state authorities to ensure the security of states is substantiated. The strategic partnership of the Russian Federation and the Republic of Armenia is based on a complex multilevel interaction of competent authorities. Achieving of strategic cooperation depends on coordinated and consistent actions of all branches of power.